2010
DOI: 10.1093/eurpub/ckq036
|View full text |Cite
|
Sign up to set email alerts
|

Maternal alcohol use and medically indicated vs. spontaneous preterm birth outcomes: a population-based study

Abstract: Prenatal alcohol use is a risk factor for preterm delivery, and especially for spontaneous preterm birth. These findings enhance our understanding of the aetiology of preterm birth and could be utilized in the development of appropriate prevention strategies that will assist in decreasing perinatal mortality and morbidity associated with preterm delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 30 publications
1
25
2
Order By: Relevance
“…Some baseline characteristics varied significantly between the countries, highlighting the diversity of the HIV-infected pregnant population and resource availability in sub-Saharan Africa. Whereas the higher risk of PTD in Zambia may be attributable to differences in maternal characteristics, such as higher parity [17], higher prevalence of syphilis [18], and higher rate of alcohol use [19], the disparity between the settings may also contribute. Syphilis and hemoglobin screening were often not done in Zambia.…”
Section: Discussionmentioning
confidence: 99%
“…Some baseline characteristics varied significantly between the countries, highlighting the diversity of the HIV-infected pregnant population and resource availability in sub-Saharan Africa. Whereas the higher risk of PTD in Zambia may be attributable to differences in maternal characteristics, such as higher parity [17], higher prevalence of syphilis [18], and higher rate of alcohol use [19], the disparity between the settings may also contribute. Syphilis and hemoglobin screening were often not done in Zambia.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, however, that no studies conducted in Asian countries were included in this meta-analysis [2]. Four studies in the USA have shown significant positive relationships between low to moderate maternal alcohol consumption during pregnancy and the risk of LBW, PTB, and/or SGA [3-6], while equally significant inverse associations have been observed in two studies in Canada and Spain [7,8]. To our knowledge, there have been only three previous studies on alcohol consumption during pregnancy and birth weight or LBW in Japan, none of which have revealed any associations [9-11]; however, no epidemiological studies in Japan have examined the association of maternal alcohol consumption during pregnancy with the risk of PTB and SGA.…”
Section: Introductionmentioning
confidence: 99%
“…For multiple linkages, the most likely potential linkage was based on the weighted score and quality of agreement indicator. The methods and algorithm used in linking vital records information into sibling relationships and the process of validation have been described in detail previously [31,32]. …”
Section: Methodsmentioning
confidence: 99%
“…The Missouri vital record system is a reliable one that has been used as the gold standard to validate U.S. national datasets that involve matching and linking procedures [32,33]. The Missouri maternally linked cohort dataset contains information on both live births and fetal deaths for each sibling and provides a platform for a longitudinal study of birth outcomes for a given cohort of mothers.…”
Section: Methodsmentioning
confidence: 99%